Cavitation funnel effect: Bio-inspired leading-edge tubercle application on ducted marine propeller blades. (November 2021) - Stark, Callum; Shi, Weichao; Troll, Moritz
Highlights: Leading-edge tubercles are applied to the blades of a benchmark ducted propeller. Cavitation volume can be reduced by up to 50%. Total thrust coefficient can be improved by a maximum 10%. Propulsive efficiency improved by a maximum of 6.5% in heavy-cavitating conditions. Abstract: Cavitation is an ever-present issue in the maritime industry as it causes damage to the propeller in the form of erosion, reducing hydrodynamic performance and increasing the underwater radiated noise (URN) level generated. Therefore, containing cavitation on marine propellers is an important area to research in order to reduce structural damage, efficiency loss and noise pollution. Recently there has been growing research in the leading-edge (LE) tubercles located on Humpback whale pectoral fins that have been attributed to give the whales superior manoeuvrability through prolonged flow attachment and have shown to improve hydrodynamic performance on marine applications. This paper assesses the sheet cavitation containment capability of the LE tubercles on a benchmark ducted propeller blade in both heavy and light cavitating conditions. The analysis is carried out over a range of operating conditions using commercial code STAR-CCM+ with the implicit unsteady Improved Delayed Detached Eddy Simulation (IDDES) method and the Schnerr-Sauer cavitation model. The investigation encompassed two tubercle designs with varying geometrical configurations of wavelength while maintaining the amplitude. In summary, it was found that LE tubercles as applied to the Kaplan propeller blade has presented a cavitation funnel effect which can successfully reduce the sheet cavitation development by a maximum of 50%, while enhancing the total thrust coefficient in all operating conditions by a maximum of 10%. Comparing at the same thrust loading coefficient, the propulsive efficiency in heavy-cavitating conditions can be improved by a maximum of 6.5%.